Per lo buono istato de la città I Servi di s. Maria nella società dell'Italia centro-settentrionale tra XIII e XIV secolo - Carletti, Emanuele (Premio Istituto Sangalli per la storia religiosa, 2023)
The volume offers a new perspective for the study of the mendicant orders between the 13th and 14th centuries through the example of the Servites in central and northern Italy. The study, despite considering a so-called 'minor' order, has made it possible to analyse two essential issues for Western Europe's late medieval history. The first concerns the transformations of religiosity between the 13th and 14th which saw the prominence of new social classes and institutions. The second concerns the urban expansion, the economic growth and the political-institutional and socio-cultural changes that characterised the cities of the time. The Servites were expression and later fine interpreters of these processes, becoming actors who were anything but marginal in the social context of late medieval Italy.